THE EFFECT OF NEW SHARE PRICE FRACTION ON LIQUIDITY - Reva Yuliani; Djoko Roespinoedji (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This research was conducted to determine the effect of the new price fraction on liquidity. The new price fraction policy implemented by the Indonesia Stock Exchange on 02 May 2016 affects 5 groups of share prices. Based on the Decree of the Board of Directors of the Indonesia Stock Exchange Number Kep-00023 / BEI / 04-2016, one of the expected impacts of this change is an increase in stock liquidity. Through purposive sampling technique, a sample of 273 companies was obtained. This study uses daily transaction data for 30 days before and after the fraction reduction. Through the Wilcoxon Signed Rating Test, it was found that a decrease in price fraction had a positive effect on relative spread and depth. To overcome the contradiction in results, the Depth to Relative Spread was calculated, which shows that a decrease in the fraction does not affect the increase or improvement in liquidity in groups 1,2,3, has no significant effect in groups 4 and 5 has a significant effect.